EKSPLORASI AKTIVITAS BUDAYA PANRE BESSI SEBAGAI KONTEKS PEMBELAJARAN GEOMETRI BERBASIS HOTS - Arsyika; Zulfikar Busrah; Azmidar (Tautologi: Journal of Mathematics Education, 2026)
This study aims to identify geometric elements in the cultural activities of Panre Bessi in the Massepe community and to describe their potential as a geometry learning context based on Higher Order Thinking Skills (HOTS). This research employed a mixed methods approach with a Sequential Exploratory Design. Data were collected through observation, interviews, and documentation involving three Panre Bessi practitioners, as well as HOTS tests administered to 18 Grade VII students of SMP Negeri 2 Tellu Limpoe. The data were analyzed descriptively. The results showed that Panre Bessi activities contain geometric elements, including circular shapes, similarity and scale, ratio and proportion, as well as changes in geometric forms during the blade-forming process. The quantitative results indicated that 11.1% of students were in the high category, 61.1% in the moderate category, and 27.8% in the low category. Students’ analytical ability (C4) was better than evaluation ability (C5), as reflected in the ability to identify geometric elements reaching 83.3%, while the ability to evaluate disproportionate tool shapes only reached 44.4%. Thus, Panre Bessi cultural activities have the potential to be used as a contextual geometry learning setting that supports students’ HOTS, especially in the aspects of analysis (C4) and evaluation (C5).